2013
DOI: 10.1590/s0102-09352013000600025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorghum tannins in sheep fed with high-concentrate diets

Abstract: The aim of this study was to evaluate the nutritional value of three sorghum cultivars with different concentrations of condensed tannins in sheep diets. Six adult sheep (LW=56kg) with rumen and duodenal fistulas were assigned to experimental groups using two 3x3 Latin Square designs. The diets were formulated using three sorghum cultivars: LTC (low-tannin cultivar), MTC (medium-tannin cultivar) and HTC (hightannin cultivar). Microbial nitrogen (MN) concentration in the duodenum was measured using a 15 N trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The present study did not find significant effect on DM digestibility, but N excretion was increased in feces and apparent CP digestibility was decreased with increasing sorghum levels. The lower digestibility of CP might be explained by the following three reasons: (i) the N intake for S treatment is higher compared with C treatment; (ii) tannins in sorghum interfere with protein digestion period, Cabral et al (2013) evaluated the nutritional values of three sorghum cultivars with different concentrations of condensed tannins in sheep diets, and found that protein digestibility was reduced with the increase of tannin content in sorghum; (iii) the structure of sorghum could decrease the digestibility of protein and starch owing to the encasement of starch granules in a protective protein matrix inside the hard peripheral endosperm layer of the grain (Rooney and Pflugfelder 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not find significant effect on DM digestibility, but N excretion was increased in feces and apparent CP digestibility was decreased with increasing sorghum levels. The lower digestibility of CP might be explained by the following three reasons: (i) the N intake for S treatment is higher compared with C treatment; (ii) tannins in sorghum interfere with protein digestion period, Cabral et al (2013) evaluated the nutritional values of three sorghum cultivars with different concentrations of condensed tannins in sheep diets, and found that protein digestibility was reduced with the increase of tannin content in sorghum; (iii) the structure of sorghum could decrease the digestibility of protein and starch owing to the encasement of starch granules in a protective protein matrix inside the hard peripheral endosperm layer of the grain (Rooney and Pflugfelder 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The voluntary feed intake of ruminants by providing plants with high condensed tannin (CT) content (usually >50 g/kg DM) can be reduced, with a moderate or low intake (<50g/kg DM) not affecting it [ 131 ]. On this side, Cabral Filho et al [ 132 ] observed no effect on DM consumption of sheep.…”
Section: Effect Of Tannins On Ruminant Nutritionmentioning
confidence: 97%
“…Ruminal pH changes affect the complexes and provide information about the function of tannins in the gastrointestinal tract [ 103 ]. Cabral Filho et al [ 132 ] investigated three levels of tannin in the diet of sheep and reported a different DM digestibility between high- and low-tannin cultivars. The low tannin content diet had a higher crude protein digestibility, and there were no significant differences between the medium tannin content and high tannin content diets.…”
Section: Effect Of Tannins On Ruminant Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the representatives of such products, of interest for production, is tannin, one of the secondary metabolites of plants. This compound is not involved in processes considered essential for plants (Cabral Filho et al, 2013). Tannins improve digestibility of nutrients, optimizing production of propionic acid, microbial protein synthesis and reduce the number of ciliate protozoa (Castro-Montoya et al, 2011;Alves Júnior et al, 2017).…”
Section: Introductionmentioning
confidence: 99%